Prevalence characteristics of pertussis from 2010 to 2022 and its projected incidence in Hangzhou city - Yingying YANG; Yan LIU; Xuechao ZHANG; Yuyang XU; Jing WANG; Wenwen GU; Jian DU; Xiaoping ZHANG; Jun WANG; Xinren CHE; Wei JIANG; Qixin XIE; et al. (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the prevalence of pertussis in Hangzhou city from 2010 to 2022 and predict its incidence rate using an autoregressive integrated moving average (ARIMA) model, with the goal of improving prevention and control measures. MethodsThe reported pertussis incidence data and population data of Hangzhou city from 2010 to 2022 were collected through the infectious disease surveillance system in the Chinese Disease Prevention and Control Information System and the Statistical Yearbooks published by the Hangzhou Statistics Bureau (http://tjj.hangzhou.gov.cn/), respectively, to analyze the epidemiological characteristics. The collected data was used to construct an ARIMA model for predicting pertussis incidence rates in the city for 2023 and 2024. ResultsA total of 2 484 pertussis cases were reported in Hangzhou city over a 13-year period, with a male-to-female ratio of 1.03 : 1 and an average annual incidence rate of 2.49 per 100 000 population. The majority of pertussis cases occurred during the summer season, with the highest monthly incidence observed in June each year. Three districts within the city exhibited high rates of pertussis incidence. Approximately half (47.34%) of the reported cases involved children aged 0 - 4 years old. Based on the optimal ARIMA(0,1,2)(0,1,1)12 model analysis results, a projected decrease in annual incidence rates is expected for both 2023 and 2024 compared to that of 2022. ConclusionThe incidence of pertussis in Hangzhou has been increasing from 2010 to 2022, and the ARIMA model can provide predictions for the incidence trend of pertussis in the city.